Colonial law in Africa, 1920-1945. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
Originally known as the 'Government Gazettes', each item contains the colonial laws for the year they were published. The legal records also include property for sale, probate records and bankruptcy notices. This is the second part of the three part series 'Colonial Law in Africa'. These records cover the transfer of Southern Rhodesia from the British South Africa Company to colonial rule. A series of legal notices also reveal the impact of the Treaty of Versailles on Tanzania. The Second World War then led to a series of new laws in these colonies. These gazettes were published alongside the African Blue Books of Statistics during the 19th and 20th centuries.
Date range: 1920-1945.
Keywords: Africa -- Politics and government -- To 1945.